Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Controls on apatite compositional variations in magmatic rocks: A case study of Mesozoic mafic–felsic intrusions from the eastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao (Journal of Asian Earth Sciences, 2024)

Recycled crustal components in the depleted mantle source: Evidence from Early Cretaceous mafic rocks in the southern margin of the North China Craton - An-Qi Wang; De-Bin Yang; Wen-Liang Xu; Hao-Tian Yang; Yi-Kang Quan; Xiang-Yu Yan; Le-Ran Hao; Feng Wang (Lithos, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

Identification of metasomatic components in lithospheric mantle under multiple tectonic regimes: Insights from Early Cretaceous mafic rocks in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Feng Wang (Lithos, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Apatite geochemistry from mafic rocks in the northeastern North China Craton: New insights into petrogenesis - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Hao-Tian Yang; Feng Wang (Lithos, 2023)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)